2019
DOI: 10.1117/1.jbo.24.2.025003
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated multimodal optical imaging system with real-time image analysis for the evaluation of oral premalignant lesions

Abstract: Kortum, "Development of an integrated multimodal optical imaging system with real-time image analysis for the evaluation of oral premalignant lesions," J.Abstract. Oral premalignant lesions (OPLs), such as leukoplakia, are at risk of malignant transformation to oral cancer. Clinicians can elect to biopsy OPLs and assess them for dysplasia, a marker of increased risk. However, it is challenging to decide which OPLs need a biopsy and to select a biopsy site. We developed a multimodal optical imaging system (MMIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…The imaging hardware is connected by USB to a touchscreen laptop, which runs the MMIS software. The MMIS has been previously described in detail; selected details are also provided in the “MMIS Hardware and Automated Analysis” section.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The imaging hardware is connected by USB to a touchscreen laptop, which runs the MMIS software. The MMIS has been previously described in detail; selected details are also provided in the “MMIS Hardware and Automated Analysis” section.…”
Section: Methodsmentioning
confidence: 99%
“…The number of abnormal nuclei/mm 2 algorithm identified individual nuclei within the image and was used to classify each nucleus as normal or abnormal based on its area and eccentricity . Nuclei with an area > 200 μm 2 , or with an area > 170.8 μm 2 and eccentricity >0.705, were considered abnormal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, studies have shown that a feature called the number of abnormal nuclei per mm 2 , calculated from HRME images, can distinguish oral cancer and highgrade dysplasia from benign tissue with high accuracy (the ND algorithm). 19,20 One limitation of in vivo microscopy in the oral mucosa is that images frequently contain regions without reliable information about nuclei. For example, leukoplakias, which are the most common oral premalignant lesion, contain a highly scattering keratin layer that overlies the epithelium and can prevent visualization of the subsurface nuclei with good contrast.…”
Section: Introductionmentioning
confidence: 99%